ASR, Volume 21, n° 1, 2017 - Full Issue - journal system, (African Sociological Review, 2017)
Contents Editorial ..............................................................1 Research Papers If it ain’t broke, don’t fix it’: Challenges facing institutional transformation of historically white South African universities Sabrina Liccardo, Masixole Booi & Louise Vincent ........................................2 Reality Checks: The state of civil society organizations in Ethiopia Yntiso Gebr .............................................................20 Migrations européennes, reconversions professionnelles et économie touristique : Les impasses de la valorisation culturelle de l’espace saint-louisien (Sénégal) Hélène Quashie ......................................................................43 Family structure and children’s schooling in sub-Saharan Africa Acheampong Yaw Amoateng, Tim. B. Heaton & Camille Mealmont ......................................77 Privatisation de la sécurité et gouvernance démocratique au Cameroun Désiré Manirakiza .....................................................99 Work reorganization and technological change: limits of trade union strategy and action at ArcelorMittal, Vanderbijlpark Mondi Hlatshwayo & Sakhela Buhlungu .............................................................126 Employment status, medical support and Income as significant factors in Access to Essential Medicines Chinwe Christopher Obuaku-Igwe ......................................................154